Prophylactic effects of Nigella sativa extract and thymoquinone against cyclophosphamide-induced sperm head abnormalities and chromatin instability in mice - Abdul Rahman, Suzanah; Kamarzaman, Saheera (Academy for Environment and Life Sciences, India, 2017)
Genetic stability in male fertility is indicated by DNA integrity of sperm. Cyclophosphamide is cytotoxic to germ cells of the testes causing DNA breakage, azoospermia and infertility. This study focuses on effectiveness of Nigella sativa and thymoquinone in lowering chemotherapeutic-associated toxicity of cyclophosphamide on sperm head and chromatin stability of Balb/c mice. Thirty male mice were divided into 6 groups and administration of cyclophosphamide at 200 mg/kg body weight by intraperitoneal injections is followed similarly by either thymoquinone or ethanol extraction of Nigella sativa at 10 mg/kg, 6 hours post cyclophosphamide exposure. Thymoquinone and Nigella sativa administration was continued on alternate days for 32 days. Sperm samples were assayed with Eosin Y and Toluidine Blue. Sperm head abnormalities were classified into normal, lack-hook, banana-like form, amorphous and folded on themselves. Chromatin condensation was categorised into unstained, completely and partially-stained. One hundred spermatozoa per animal were observed. Nigella sativa extract reduced the percentage of abnormal sperm head post-cyclophosphamide treatment and showed preservation of the normal chromatin condensation indicative of protection against sperm DNA alteration. This study indicates the potential of Nigella sativa and thymoquinone as prophylaxes against cyclophosphamide-induced damage to gametes in the attempt to salvage reproductive functions following chemotherapy.